2020
DOI: 10.3390/nu12103191
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Perception of Distance to the Grocery Store as a Reason for Feeling Food Insecurity—Can Food Policy Limit This?

Abstract: The sense of food insecurity in a group of elderly people may be determined by the perception of distance to food outlets. The aim of the study was to assess the relationship between the perception of food insecurity by the elderly and their perception of the distance between the places of residence and food purchase. A cross-sectional quantitative survey was carried out in 2019–2020 amongst 762 Polish elderly living in Świętokrzyskie and Śląskie Voivodeship. The assessment of the relationships between the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
(83 reference statements)
0
16
0
1
Order By: Relevance
“…In Poland, supermarkets are mostly located in cities, so their accessibility for people from rural areas is potentially more limited than for city residents, although this study did not assess participants’ mobility options. Nevertheless, lower accessibility to food products due to the commuting distance of the residence from the place where the food is purchased, especially among rural residents, was confirmed in another survey [ 55 ]. A large distance between the place of residence and the outlets resulted in a lack of products such as fish and fish products, some fruits, beef meat, and some vegetables in the daily diet [ 56 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Poland, supermarkets are mostly located in cities, so their accessibility for people from rural areas is potentially more limited than for city residents, although this study did not assess participants’ mobility options. Nevertheless, lower accessibility to food products due to the commuting distance of the residence from the place where the food is purchased, especially among rural residents, was confirmed in another survey [ 55 ]. A large distance between the place of residence and the outlets resulted in a lack of products such as fish and fish products, some fruits, beef meat, and some vegetables in the daily diet [ 56 ].…”
Section: Discussionmentioning
confidence: 95%
“…Another Polish study in a group of elderly people has shown that as many as one-fifth of the respondents did not use social assistance, despite their financial problems. Nonetheless, the region was more important than the place of residence in differentiating the use of such assistance, which may result from the different availability of such assistance, but also from the varying cultural backgrounds [ 55 ]. In this study, in particular low SES and living in a large city meant experiencing greater food insecurity, indicating the need to include this group in social assistance provided to the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de las limitaciones de esta investigación se encuentran el diseño trasversal, que no permite inferir causalidad; la muestra de la población am del proyecto marco, que no fue representativa de la ciudad, y la isa, que se enfocó solo en la falta de recursos económicos, pues en otros estudios [21,41] se han considerado otras causas, como la incapacidad para comprar alimentos o cocinar, lo que puede llevar a subreporte de isa en esta población.…”
Section: Discussionunclassified
“…Another issue is the accessibility of food, which can occur for different issues depending on the life cycle. Elderly people report ( 21 , 26 ) having more difficulty walking long distances to shop, carry groceries, or carry heavy bags, while younger adults report lack of money as a limiting cause to access food. Russell et al ( 21 ) suggest that poor physical functionality can be a major limitation for older people to acquire or prepare food appropriately.…”
Section: Discussionmentioning
confidence: 99%